Use of Adjunct Antiseptic Agents in Periprosthetic Joint Infections. Issue 23 (1st December 2021) - Plate, Johannes F.; Zuskov, Andrey; Seyler, Thorsten M.
Abstract : Periprosthetic joint infection is a leading cause for failure of contemporary total hip arthroplasty and total knee arthroplasty projected to nearly double in the next decade and reach an economic burden of $1.85 billion in the United Sates by 2030. Although multiple treatments for periprosthetic joint infection have been described, a thorough débridement and joint lavage to decrease bacterial bioburden and to remove biofilm remains a critical component of treatment. Various adjunct antiseptic agents such as chlorhexidine, povidone-iodine, hydrogen peroxide, acetic acid, and chlorine compounds are currently in off-label use in this capacity. Each antiseptic agent, however, has a distinct mechanism of action and targets different organisms, and some combinations of agents may lead to tissue toxicity. In this review, currently available adjunct antiseptic washes will be described in detail based on their mechanism of action and the evidence for their use will be reviewed. Furthermore, this review puts forward an evidence-based treatment algorithm based on the specific causative organism.